ISMIP6 Antarctica: a multi-model ensemble of the Antarctic ice sheet evolution over the 21st century - Seroussi, Hélène; Nowicki, Sophie; Payne, Antony; Goelzer, Heiko; Lipscomb, William; Abe-Ouchi, Ayako; Agosta, Cécile; Albrecht, Torsten; Asay-Davis, Xylar; Barthel, Alice; Calov, Reinhard; Cullather, Richard; et al. (The Cryosphere, 2020)
International audience